Steroid cell tumor : A rare ovarian tumor: Case Report - Patel, Falguni T.; Shah, Bhoomi A.; Parikh, Nisarg R.; Gonsai, Ratigar N. (Annals of Pathology and Laboratory Medicine, 2019)
Steroid cell tumors of ovary are a rare subgroup of sex cord tumors, account less than 0.1% of all ovarian tumors and also will present at any age. Some of this tumor may be functional and secrete hormones. Nearly 56-77% of the cases present with hypergonadism. However, there may be atypical presentations of these tumors also when they do not show any symptoms of virilization. In these cases diagnosis is usually made postoperatively on finding a tumor in ovary. A careful correlation between Clinical and surgical evaluation and microscopic analysis is necessary, as is a regular follow up. We reported a case of 45 years old female with complained of abdominal pain on & off since two years. She had no other complains. Histopathology confirmed the diagnosis of steroid cell tumor not otherwise specified type (NOS type) with no cytological atypia.